2020
DOI: 10.1038/s41598-020-75608-2
|View full text |Cite
|
Sign up to set email alerts
|

High prevalence of mcr-1-encoded colistin resistance in commensal Escherichia coli from broiler chicken in Bangladesh

Abstract: Colistin is a last-resort antimicrobial used for the treatment of human infections caused by multidrug-resistant Gram-negative bacteria. However, colistin is still widely used in intensive poultry production in Bangladesh. We aimed to investigate the dynamics and genetic diversity of colistin-resistant commensal Escherichia coli from broiler chickens. A total of 1200 E. coli strains were characterized from 20 broiler farms at three-time points along the production period. All strains were screened for mcr-1 to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
35
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 38 publications
(38 citation statements)
references
References 74 publications
2
35
1
Order By: Relevance
“…Various species of Enterobacteriaceae carrying mcr-1 plasmid-mediated resistance have been identified from humans, animals and environments in Asia, Europe, Africa, North America and South America [ 51 ]. Furthermore, the proportion of mcr-1 carriers among colistin-resistant isolates was higher in food-producing animals investigated in Italy [ 52 ], Germany [ 53 ], UK [ 54 ], Poland [ 55 ], Bangladesh [ 56 ], India [ 57 ], Pakistan [ 58 ], and South Korea [ 59 ]. Interestingly, the detection of the colistin resistance mcr-1 gene associated with the risk of subsequent transmission to unexposed human populations in southern Vietnam was also reported [ 60 ].…”
Section: Discussionmentioning
confidence: 99%
“…Various species of Enterobacteriaceae carrying mcr-1 plasmid-mediated resistance have been identified from humans, animals and environments in Asia, Europe, Africa, North America and South America [ 51 ]. Furthermore, the proportion of mcr-1 carriers among colistin-resistant isolates was higher in food-producing animals investigated in Italy [ 52 ], Germany [ 53 ], UK [ 54 ], Poland [ 55 ], Bangladesh [ 56 ], India [ 57 ], Pakistan [ 58 ], and South Korea [ 59 ]. Interestingly, the detection of the colistin resistance mcr-1 gene associated with the risk of subsequent transmission to unexposed human populations in southern Vietnam was also reported [ 60 ].…”
Section: Discussionmentioning
confidence: 99%
“…Despite the low prevalence of the mcr-1 gene, the frequent contamination of poultry carcasses with intestinal contents during the slaughter process has been reported 24) . A study conducted in Bangladesh found high prevalence (25%) of the mcr-1 gene in E. coli isolated from broiler chickens, and this finding was associated with high CST usage for treatment and prophylaxis purposes 32) . In addition, a survey in the Netherlands detected the mcr-1 gene (8%) in chicken 15) .…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, the use of colistin in broilers and pigs has been shown to lead to the emergence of colistin-resistant E. coli isolates whereas initially, those isolates were sensitive to colistin [ 5 , 16 ]. Colistin-resistant isolates (positive mcr-1 ) are more likely to be found in samples of animal origin rather than human origin [ 17 ]. However, their prevalence in sewage treatment plants is yet mainly unknown [ 18 ].…”
Section: Discussionmentioning
confidence: 99%